EFFECT OF ATMOSPHERIC TEMPERATURE ON THE DEVELOPMENT OF RED ROT OF SUGARCANE - SATYAVIR, M. S. BENIWAL AND (Indian Phytopathology, 2002)
Red rot development by plug method of inoculation decreased with the decrease in mean temperature from 31.0 to 21. 1Â°C. It was more pronounced in clones COS 802, S77/467, Co 1158 and Co J 64 in comparison to resistant Co 7314 and highly susceptible clones Co L 29 and S78/56O. Top drying was highly responsive to variation in temperature as compared to disease index. Red rot development was optimum between the temperature range of 29.4-31.O"C during the months of August and first week of September under Hisar conditions.